2014
DOI: 10.3390/cells3040939
|View full text |Cite
|
Sign up to set email alerts
|

Classical Transient Receptor Potential 1 (TRPC1): Channel or Channel Regulator?

Abstract: In contrast to other Classical Transient Receptor Potential TRPC channels the function of TRPC1 as an ion channel is a matter of debate, because it is often difficult to obtain substantial functional signals over background in response to over-expression of TRPC1 alone. Along these lines, heterologously expressed TRPC1 is poorly translocated to the plasma membrane as a homotetramer and may not function on its own physiologically, but may rather be an important linker and regulator protein in heteromeric TRPC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 121 publications
1
69
0
Order By: Relevance
“…TRPC1 does not fit into this pattern as it might not form functional homotetrameric channels [45,73]. TRPC1 can associate with all TRPC isoforms [45,61,73,97,120,160,161,178,184], as well as with TRP proteins from other TRP sub-families, such as TRPP2, TRPV1, TRPV4 and TRPV6 [50,147]. Moreover, TRPC1 is suggested to assemble with other proteins like Stim1 [125,132] and caveolin-1 [131,140,163].…”
Section: Trpc Channels In the Pulmonary Vasculaturementioning
confidence: 93%
See 2 more Smart Citations
“…TRPC1 does not fit into this pattern as it might not form functional homotetrameric channels [45,73]. TRPC1 can associate with all TRPC isoforms [45,61,73,97,120,160,161,178,184], as well as with TRP proteins from other TRP sub-families, such as TRPP2, TRPV1, TRPV4 and TRPV6 [50,147]. Moreover, TRPC1 is suggested to assemble with other proteins like Stim1 [125,132] and caveolin-1 [131,140,163].…”
Section: Trpc Channels In the Pulmonary Vasculaturementioning
confidence: 93%
“…TRPC3, TRPC6 and TRPC7 are suggested to assemble and form ROC, gated by diacylglycerol (DAG) derived from C-type phospholipase (PLC)-mediated hydrolysis of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) [42]. TRPC1 does not fit into this pattern as it might not form functional homotetrameric channels [45,73]. TRPC1 can associate with all TRPC isoforms [45,61,73,97,120,160,161,178,184], as well as with TRP proteins from other TRP sub-families, such as TRPP2, TRPV1, TRPV4 and TRPV6 [50,147].…”
Section: Trpc Channels In the Pulmonary Vasculaturementioning
confidence: 97%
See 1 more Smart Citation
“…It appears, based on the current body of scientific research, that different members of this subfamily are activated based on one or both of these two methods depending on the expression system, expression level and the antibody used. Other research has also suggested mechanosensitive gating mechanisms (Dietrich et al 2014). In spite of these experimental limitations, much is known about this subfamily of TRP channels.…”
Section: Trpc Subfamilymentioning
confidence: 98%
“…TRPC channels have been shown to form both heterotetramers and homotetramers within the TRP channel superfamily, with different members having certain preferences, for example, TRPC1 forms physiologically relevant functional channels with several TRPC channels including TRPC4, as well as, TRPV1, and TRPP2 (Ong et al 2016; Dietrich et al 2014). …”
Section: Trpc Subfamilymentioning
confidence: 99%